MANIPULASI HABITAT SEBAGAI SOLUSI TERJADINYA OUTBREAK WERENG COKLAT - Retno Wijayanti; Supriyadi Supriyadi; Wartoyo Wartoyo (Caraka Tani: Journal of Sustainable Agriculture, 2012)
Brown plant hopper outbreaks occurred again in the growing season of 2009 and continues to the present (2011). As a result of brown pant hopper, rice plants be comepuso. It is estimated more than 70% areal the rice in the ‘Golden Triangle’, name Klaten, Boyolali, and Sukoharjo crop failure. The main factors causing a population explosion is not the proper functioning of natural enemies. Natural enemies of brown pant hopper of dying from unwise use of pesticides. Actual mortality could be reduced if the natural enemies, natural enemies have a place of refuge from exposure topesticides by increasing habitat diversity in agricultural land. Research carried outaiming to see the effect of habitat manipulation in the presence of natural enemies and maintain the stability of the rice field ecosystem. The study was conducted at two locations namely rice land in the area and in Klaten Ceper Karanganom, Klaten. The results showed that the brown plant hopper populations relatively low throughout the study so it is not showing signs of damage. Natural enemy population is quite high in both locations experiments. Index of species diversity in Ceper experimental result show a high relative value. Results while the second experiment (in Karanganom) showed that land with habitat manipulation has a population of natural enemies and other insects is higher than the land without habitat manipulation.